Effects of a major structural change to the intensive care unit on the quality and outcome after intensive care. Issue 4 (1st August 2005) - Flaatten, H
Abstract : Background: Changes in structure may affect outcome after intensive care in various ways. Both closed (as opposed to open) units and the number of nurses have been shown to affect outcome. Objective: To study the effects of temporarily moving an intensive care unit (ICU) on various indicators of outcome and quality of care. Methods: Because of rebuilding, over a period of 8 months our ICU was moved to an adjacent postoperative area. The 12 month periods immediately before and after the rebuilding were chosen as reference periods. Routinely collected data such as length of stay, ventilator time, readmission rate, severity score (SAPS II), and observed mortality were used for comparison. Results: Using variable life adjusted display (VLAD), an increase in hospital mortality was observed during the 8 month rebuilding period. This was also found using Kaplan-Meier estimates of survival and standardised mortality ratio. Conclusion: Structural change to our ICU was probably the major cause for the observed change in mortality.